An evaluation of direct seeding for reforestation of degraded lands in central São Paulo state, Brazil - Engel, Vera Lex [UNESP]; Parrotta, J. A. (Elsevier B.V., 2001)
As part of a larger study evaluating several silvicultural techniques for restoring tropical moist forests on abandoned agricultural lands in southeastern Brazil, direct seeding with five early-successional Atlantic forest species was tested at three degraded sites, characterized by different soil types and land-use histories, within the Environmental Protection Area at Botucatu, SP. The species used in this study were Chorisia speciosa, Croton floribundus, Enterolobium contorstisiliquum, Mimosa scabrella, and Schizolobium parahyba. Scarified seeds of each of these species were sown in prepared seed spots in replicated, 0.25 ha mixed-species plots at an initial espacement of 1 m x 1 m at each site. of the five species planted, only two, Enterolobium and Schizolobium, showed good seed germination, seedling survival, and early growth rates, averaging 4.1-4.6 cm stem diameter and 1.5-1.7 m height growth during the first 2 years after sowing. These two species constituted 88-100% of the total stand density, which ranged from 1050 to 1790 stems ha(-1) at 2 years. Despite the poor performance of the other species tested, we observed that the natural regeneration of native forest species originating from remnant forests in the general vicinity of our study sites was significantly greater within the direct-seeded plots than in unplanted control plots that were protected from fire and other disturbances. Published by Elsevier B.V. B.V.
Keywords: forest restoration; native species; natural regeneration; seedling growth; tropics